The Consumer Psychology of Microtransactions in Free-to-Play Games : The behavioural economics perspective - Salakari, Pessi (My University, 2024)
The swiftly growing, lucrative and yet unmature industry of video games has seen significant shifts in revenue generation strategies trough the recent decades. Especially the recent mass shift to the free-to-play model has brought with it various new, complex and unexplored monetization forms that ought to be studied extensively. This thesis examines the role of behavioural economics in these enigmatic microtransactions in free-to-play games, integrating relevant theories such as prospect theory and social proof. The thesis begins by exploring the historical context of free-to-play games and proceeds by defining the current state of the market and its most influential monetization forms such as loot boxes and the battle pass. After presenting the various theories of behavioural economics, the study integrates them into the context of free-to-play monetization forms. Through structured analysis of these monetization forms, the thesis uncovers the depth of the psychological fallacies related to consuming in these virtual environments. This thesis found various links between the discussed theories and microtransactions and uncovered certain ethically questionable psychological fallacies in play. Ultimately the thesis contributes to a deeper understanding on this form of virtual consumption, shedding light on the matter through frameworks of behavioural economics, benefitting consumers, managers, parents and academics alike.

Nopeasti kasvava, tuottoisa mutta vielä kypsymätön videopeliteollisuus on kokenut merkittäviä muutoksia ansaintamalleissaan viime vuosikymmenten aikana. Erityisesti viimeaikainen laajamittainen siirtymä ilmaispelimalliin on tuonut mukanaan uusia, monimutkaisia ja osin tutkimattomia kaupallistamisen muotoja, joita on syytä tutkia perusteellisesti. Tämä kanditutkielma tarkastelee käyttäytymistaloustieteen roolia näissä osalti arvoituksellisissa ilmaispelien mikrotransaktiomalleissa. Tutkielma hyödyntää relevantteja teorioita, kuten prospektiteoriaa ja sosiaalista todisteisuutta. Tutkielma alkaa tarkastelemalla ilmaispelien historiallista kontekstia ja etenee määrittelemään markkinoiden nykytilan sekä sen merkittävimmät kaupallistamisen muodot, kuten ”loot boxes” ja ”the battle pass”. Käyttäytymistaloustieteen eri teorioiden esittelyn jälkeen teoriat integroidaan ilmaispelien kaupallistamismuotojen kontekstiin. Rakenteellisen analyysin avulla tutkielma tuo esiin näihin virtuaalisiin ympäristöihin liittyvien kulutustottumusten psykologisten vinoumien syvyyden. Tutkielma löysi useita yhteyksiä käsiteltyjen teorioiden ja mikromaksujen välillä ja paljasti tiettyjä eettisesti kyseenalaisia psykologisia vinoumia. Kaiken kaikkiaan tutkielma syventää ymmärrystä tästä virtuaalisesta kulutusmuodosta valaisten ilmiötä käyttäytymistaloustieteen viitekehysten kautta ja tarjoten hyötyä niin kuluttajille, johtajille, vanhemmille kuin akateemiselle tutkimuksellekin.
Keywords: video games, virtual consumption, microtransactions, behavioural economics, consumer psychology, purchase behaviour, battle pass, loot box, prospect theory, social proof, videopelit, virtuaalinen kuluttaminen, mikrotransaktiot, käyttäytymistaloustiede, kuluttajapsykologia, ostokäyttäytyminen, battle pass, loot box, prospektiteoria, sosiaalinen todisteisuus